ACVIM small animal consensus statement on safe use of cytotoxic chemotherapeutics in veterinary practice. (30th March 2018) - Smith, Annette N.; Klahn, Shawna; Phillips, Brenda; Parshley, Lisa; Bennett, Peter; Flory, Andi; Calderon, Rosemary
Abstract : The purpose of this report is to offer a consensus opinion of ACVIM oncology diplomates and technicians on the safe use of cytotoxic chemotherapeutics in veterinary practice. The focus is on minimizing harm to the personnel exposed to the drugs: veterinary practitioners, veterinary technicians, veterinary staff, and pet owners. The safety of the patient receiving these drugs is also of paramount importance, but is not addressed in this statement. Much of the information presented is based on national recommendations by Occupational Safety and Health Administration, National Institute for Occupational Safety and Health, United States Pharmacopeia, and other published regulations. These directives reflect an abundance of caution to minimize exposure to medical personnel, but large‐scale studies about the consequences of long‐term occupational exposure are not available in veterinary medicine. Challenges in the delivery of optimal treatment safely and economically to veterinary patients in general practice without access to a veterinary oncologist or other specialist, because of costs or proximity, remain.